الاتجاهات المعاصرة للتحليل المالي ودورها في الحد من المخاطر المالية: دراسة ميدانية على عينة من البنوك التجارية المدرجة بسوق الخرطوم للأوراق المالية - عثمان، عبدالرحمن عادل خليل; أحمد، مزمل الحاج موسى (مركز السنبلة للبحوث والدراسات, 2022)
تناولت الدراسة الاتجاهات المعاصرة للتحليل المالي ودورها في الحد من المخاطر المالية. حيث تمثلت مشكلة الدراسة في أن التحليل المالي يعتبر خطوة ذات أهمية للمؤسسات المالية ولا يقتصر دور التحليل في جانب تقييم الأداء المالي فقط بل يتعدى ذلك إلى جوانب في الحد من المخاطر المالية. هدفت الدراسة إلى التعرف على العلاقة بين التحليل المالي والمخاطر المنتظمة، والتعرف على العلاقة بين التحليل المالي والمخاطر غير المنتظمة. اختبرت الدراسة الفرضيات الآتية: توجد علاقة ذات دلالة إحصائية بين التحليل المالي والمخاطر المنتظمة، توجد علاقة ذات دلالة إحصائية بين التحليل المالي والمخاطر غير المنتظمة. توصلت الدراسة إلى النتائج الآتية: عملت استخدام نسب رأس المال العامل إلى إجمالي الأصول الملموسة في الحد من المخاطر المالية في البنوك التجارية، ساعد استخدام نسبة صافي المبيعات إلى مجموع الأصول الملموسة في الحد من المخاطر المالية للبنوك التجارية، عملت استخدام نسب التدفق النقدي إلى مجموع الأصول في الحد من المخاطر المالية للبنوك التجارية. أوصت الدراسة بالآتي: ضرورة أن توجد الاتجاهات المعاصرة للتحليل المالي على التأكد من قدرة البنوك على سداد الأقساط في تواريخها المحددة، أن تعمل على استخدام نسبة صافي المبيعات إلى مجموع الأصول الملموسة للحد من المخاطر المالية في البنوك التجارية، ضرورة أن تجد الاتجاهات المعاصرة وسيلة للحد من زيادة في الديون عن الأصول للحد من المخاطر المالية لدى البنوك التجارية. The study deals with contemporary trends in financial analysis and their role in reducing financial risks. Where the problem of the study was that financial analysis is an important step for financial institutions, and the role of analysis is not limited to the aspect of evaluating financial performance only, but also goes beyond that to aspects in reducing financial risks. The study aimed to measure the relationship between financial analysis and systemic risks, and to identify the relationship between financial analysis and unsystematic risks. The study tested the following hypotheses: There is a statistically significant relationship between financial analysis and systemic risks, and there is a statistically significant relationship between financial analysis and unsystematic risks. The study found: The use of working capital ratios to total tangible assets helped reduce financial risks in commercial banks. The use of the ratio of net sales to total tangible assets helped reduce the financial risks of commercial banks. The use of cash flow ratios to total assets worked. In reducing the financial risks of commercial banks. The study recommended the following: The need for contemporary trends of financial analysis to ensure the ability of banks to pay installments on their specified dates, to work on using the ratio of net sales to total tangible assets to reduce financial risks in commercial banks, the need for contemporary trends to find a way to reduce An increase in debt over assets to reduce the financial risk of commercial banks.
Keywords: البنوك التجارية -- الائتمان المصرفي -- التحليل المالي -- الفشل المالي -- السودان